Youth perception of difficulty accessing cannabis following cannabis legalization and during the early and ongoing stages of the COVID-19 pandemic: repeat cross-sectional and longitudinal data from the COMPASS study - Scott T. Leatherdale; Angelica Amores; Richard E. Bélanger; Kate Battista; Karen A. Patte; Ying Jiang (BMC, 2023)
Abstract Background Very little research has examined how perceptions of cannabis access among underage youth in Canada have changed since cannabis was legalized and since the onset of the COVID-19 pandemic. As such, this paper examines the effect of the early and ongoing stages of the COVID-19 pandemic period on youth perceptions of cannabis access over time since the onset of the Cannabis Act in 2018 in a large sample of Canadian youth. Methods Using data from the COMPASS study (T1:2018/19, T2:2019/20, T3:2020/21), we used both repeat cross-sectional data [T1 (n = 38,890), T2 (n = 24,109), and T3 (n = 22,795)] to examine overall trends in perceptions of cannabis access, and sequential cohort longitudinal data [n = 4,677 students linked from T1 to T3] to examine the differential changes in perceptions of cannabis access among students over time. Results In the cross-sectional sample, the frequency of students reporting that cannabis was easy to access decreased by 26.7% from T1 (51.0%) to T3 (37.4%), although respondents who have used cannabis were more likely to report access was easy. In the longitudinal sample, perceptions of cannabis access being easy increased over time, especially among cannabis users. Perceived ease of access appears to have been slightly impeded during the initial pandemic period but rebounded during the ongoing pandemic period. Conclusions While the prevalence of youth reporting that cannabis is easy to access has declined since legalization and throughout the early and ongoing pandemic periods, a substantial number of underage youth continue to report that cannabis is easy to access. This suggest that there is an ongoing need for continued cannabis control efforts to address this issue.